An evaluation of a pilot of daily testing of SARS-CoV-2 contacts in acute hospital and ambulance trusts in England. (August 2022) - Bow, S.M.A.; Goddard, A.; Cope, G.; Sharp, N.; Schick, J.; Woods, C.; Jeffery, K.; Harrington, D.; Williams, S.; Rodger, A.J.; Finer, S.; Fowler, T.; et al.
Abstract: Objectives: Healthcare worker (HCW) SARS-CoV-2 contacts in England have been required to quarantine, creating staff shortages. We piloted daily contact testing (DCT) to assess its feasibility as an alternative. Study design: Observational service evaluation. Methods: We conducted an observational service evaluation of 7-day DCT using antigen lateral flow devices (LFDs) at four acute hospital trusts and one ambulance trust in England. Mixed methods were used, using aggregate and individual-level test monitoring data, semi-structured interviews, and a survey of eligible contacts. Results: In total, 138 HCWs were identified as contacts of a confirmed SARS-CoV-2 case. Of these, 111 (80%) consented to daily LFD testing, of whom 82 (74%) completed the required programme without interruption and 12 (11%) completed with interruption. Fifty-eight participants (52%) and two non-participants (7.4%) completed the survey. In total, 28 interviews were conducted with participants, site and infection control leads, and union representatives. One participant tested positive on LFD and polymerase chain reaction (PCR) test. Three participants tested positive on PCR but not LFD. DCT was well-accepted by trusts and staff. Participants reported no relaxation of their infection prevention and control behaviours. No incidents of transmission were detected. An estimated 729 potential days of work absence were averted. Conclusions: DCT can be acceptably operated in a healthcare setting, averting quarantine-related work absences in HCW SARS-CoV-2 contacts. Graphical abstract: Image 1